Hubungan Implementasi Perawatan Luka Dengan Kepuasan Pasien Penderita Diabetes Melitus Tipe Ii Di Wilayah Kerja Puskesmas Sungai Limau Tahun 2023 - Sri Ameliati; Suherlina; Fajri Febrini Aulia (Sekolah Tinggi Ilmu Kesehatan (STIKes) Piala Sakti Pariaman, 2023)
Diabetes Mellitus is a chronic disease in the form of metabolic disorders characterized by an increase in blood sugar levels due to disruption of insulin in the body. The prevalence of Diabetes Mellitus (DM) is increasing every year, including in Indonesia. Patients with Type II DM need the implementation of wound care to speed up the wound healing process and prevent infection in the wound. The implementation of wound care has a direct impact on patient satisfaction. This study aims to determine the relationship between the Implementation of Wound Care and Patient Satisfaction with Type II Diabetes Mellitus in the working area of the Sungai Limau Health Center in 2023. This research includes quantitative research with the type of Descriptive Correlation with a cross sectional approach. This research was conducted in the working area of the Sungai Limau Health Center in 2023 from September 25 to October 5, 2023. The population in this study is Type II DM Patients in the Sungai Limau Health Center work area recorded from January-June 2023 with a sample of 33 respondents using the Purposive Sampling technique. Most of the wound care implementation results were in moderate severity as many as 14 respondents (42.4%). Most Type II Diabetes Mellitus Patients Satisfied with the implementation of wound care were 24 respondents (72.7%). The results of statistical analysis showed a significant relationship between Wound Care Implementation and Patient Satisfaction, with p values of 0.029 < 0.05. So it can be concluded that there is a significant relationship between the Implementation of Wound Care and Satisfaction of Type II Diabetes Mellitus Patients. Advice for wound care workers in the Sungai Limau Health Center work area to maintain and improve the Implementation of Wound Care so that patients become more satisfied with the wound care provided.